Non-wood forest Produce in Village Economy - a Case Study in Chotanagpur Region - Vidyarthy, A. K.; Gupta, H. S. (Indian Forester, 2002)
This study shows that NWFP play a key role in the life and economy of communities living in and around forest. Nearly 49 items of NWFP were found to sustain people (especially the landless and marginalised groups) during lean season in the form of food, fodder, fibre, household articles, medicinal and ornamental form and supplement their income during other seasons, besides catering to religious and aesthetic needs.